2016
DOI: 10.1109/tit.2016.2550478
|View full text |Cite
|
Sign up to set email alerts
|

Large Sets of Orthogonal Sequences Suitable for Applications in CDMA Systems

Abstract: In this paper, we employ the so-called semi-bent functions to achieve significant improvements over currently known methods regarding the number of orthogonal sequences per cell that can be assigned to a regular tessellation of hexagonal cells, typical for certain code-division multiple-access (CDMA) systems. Our initial design method generates a large family of orthogonal sets of sequences derived from vectorial semibent functions. A modification of the original approach is proposed to avoid a hard combinator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Due to their almost optimal nonlinearity, semi-bent functions can resist linear approximation attacks [25,36] and fast correlation attacks [37] (assuming they possess a suitable resiliency order) when used in symmetric ciphers. Furthermore, semi-bent functions can be used to construct orthogonal variable spreading factor codes which are suitable for applications in synchronous CDMA communication systems [31,48,49].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their almost optimal nonlinearity, semi-bent functions can resist linear approximation attacks [25,36] and fast correlation attacks [37] (assuming they possess a suitable resiliency order) when used in symmetric ciphers. Furthermore, semi-bent functions can be used to construct orthogonal variable spreading factor codes which are suitable for applications in synchronous CDMA communication systems [31,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Johansson and Pasalic [32] constructed the MM class of balanced correlation immune plateaued functions, which can be vectorial semi-bent functions under certain conditions. Zhang et al [49] showed that (n, n/2 + 1) vectorial semi-bent functions (stemming from the MM class) can be used to construct the orthogonal sequence sets suitable for applications in CDMA systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cross-correlation of the sequences in a given cell between non-neighboring cells should be sufficiently small and lie in the range [2 m/2 , 2 (m+2)/2 ]. A usual way of constructing spreading codes in these systems is to use correlation-constrained sets of Hadamard matrices [7,8,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The so-called re-use distance D reflects the ability to use the same codewords in non-adjacent cells that are at distance D from the cell where these codewords have originally been placed. The re-use distance is discussed in detail in [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…This class of functions has a wide range of applications such as cryptography, in the design of sequences for communications, and related combinatorics and designs. For instance, vectorial plateaued functions were efficiently used to provide large sets of orthogonal binary sequences suitable for CDMA (Code Division Multiple Access) applications which resulted in a significant improvement of the number of users per cell in regular hexagonal networks [25]. The design methods of plateaued functions have been addressed in several works in the past twenty years [2,5,22,16,9,19,23,27], but none of these construction methods is generic and furthermore a simple characterization of these functions in the Walsh domain has not been utilized as a construction rationale.…”
Section: Introductionmentioning
confidence: 99%